Study of Soil Physical Properties Based on Land Use Units for Agriculture (Ricefield, Dryland, and Moorland) - Alexandra Neovita Tanaya; Maroeto Maroeto; Purwadi Purwadi (The University of Lampung, 2025)
Sub-watersheds are formed from the interaction process of soil-forming factors such as geology, topography, and organisms. Each interaction process results in different characteristics of soil physical properties. Physical characteristics can serve as the main reference in planning, implementing, and evaluating appropriate management of Sub watershed Areas. The purpose of this study is to examine the characteristics of soil physical properties in the Manten Sub-watershed. This research uses an exploratory approach with a field survey approach through 3 stages of activities, namely pre-survey, survey, and post survey. Each land use was repeated five times to represent the area of each land use. The parameters observed include texture, bulk density, particle density, permeability, and porosity. The results show that the physical properties of the soil in the Catchment area of the Manten Sub-watershed, Malang Regency, are very different in each land unit. Soil texture is dominated by the loam class (T1, T4, T5, S1, S2, S3, K3, and K4). Based on the research results of soil physical properties in the catchment area of the Manten sub watershed, moorland use has better soil physical properties than dry field and paddy field land uses. The poor soil physical properties in dry field and paddy field land uses may be caused by excessive land cultivation and low soil organic matter content. Keywords: Catchment area, Land use unit, Soil physical, Sub-Watershed.